THE EFFECTIVENESS OF CURRICULUM OF ISLAMIC EDUCATION MANAGEMENT PROGRAM FOR ITS USERS AND STAKE HOLDER ( Critical Review towards the Curriculum of Study Program of Islamic Education Management of UNISNU Jepara ) - Haryanto Haryanto (Universitas Islam Nahdlatul Ulama Jepara, 2017)
This descriptive research aims at describing the effectiveness of curriculumof Islamic Education Management Postgraduate Program at UNISNUJepara and contributing the critical review towards the corcordance ofcurriculum structure and subjects’ variant offered connected to stake holderand the profession of users. Qualitative method is applied in this research,whereas the technique of selecting the subject of research is purposivesampling. The data of this research are collected through interview,observation, and documentation. The result shows that the variant ofcourses that are offered by the postgraduate program are categorized to be supporting enough for the concentration Islamic education supervisionin the case of education management study program. However, some subjects need to be reviewed in curriculum review to enhance their effectiveness for users and stake holder of institutional and Islamic educationmanagement at UNISNU Jepara. Penelitian deskriptif ini bertujuan menjelaskan keefektifan kurikulummanajemen pendidikan Islam perogram pascasarjana Unisnu Jepara danmemberikan kontribusi berupa tinjauan kritis terhadap kesesuaian dalamstruktur kurikulum dan berbagai pihak yang berhubungan denganpemangku kepentingan dan profesi para pemakainya. Penelitian inimenerapkan metode kualitatif, sedangkan teknik pemilihan data denganmenggunakan tehnik sampel terpilih. Data penelitian dikumpulkan melaluiwawancara, observasi dan dokumentasi. Hasil penelitian menunjukkanbahwa ragam mata kuliah yang ditawarkan dapat dikategorikan cukupmendukung konsentrasi supervisi pendidikan Islam dalam penjurusan program studi,namun sebagian mata kuliah perlu ditinjau ulang dalamtinjauan kurikulum untuk meningkatkan keefektifannya khususnya bagi para pemangku kepentingan lembaga dan manajemen pendidikan IslamUNISNU Jepara.